Korelasi Supervisi Kepala Sekolah Terhadap Kompetensi Pedagogik dan Kompetensi Profesional Guru Sekolah Dasar - Herry Sanoto; Meutia Shafa Prastania (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
This study aims to determine the relationship between the principal's academic supervision on the professional competence and pedagogic competence of elementary school teachers. This study uses a quantitative approach, using statistical methods and descriptions. The data analysis technique used the Spearman rank RHO correlation test. Three instruments are used in this study, namely educational supervision instruments, professional competencies, and pedagogic competencies. This study used 10 random samples with the sample criteria being elementary school teachers. The results of this study indicate that there is a strong, significant, and positive relationship between the implementation of academic supervision and the professional competence and pedagogic competence of elementary school teachers